(untitled) (Research, Society and Development, 2022)
The emerging concepts in the area of Geography, such as region, network and territory, support the organization of the Unified Health System (SUS), both with regard to the coverage of technical services and health education practices. Given this, this essay presents a critical discussion about the importance of dynamics and theoretical frameworks that involve the concept of territory and, more precisely, territorialities in the contexts of Primary Care and health education. The objective is to promote reflections, considering the territorial dynamics and educational practices related to health. To this end, a narrative review of the literature was carried out, focusing on emerging productions in the fields of Geography, Health and Education that are aligned with the theme. From this, the centrality of territorialities was highlighted, as spatial dynamics, in health and education practices. As it is a concept that addresses power relations, the understanding of territoriality, which make up the territories, needs to be taken into account for the improvement of health actions and, consequently, for the enhancement of actions promoted by professionals with users of the SUS.